A Multicenter Evaluation of Survival After In-Hospital Cardiac Arrest in Coronavirus Disease 2019 Patients. (14th May 2021) - Bhardwaj, Abhishek; Alwakeel, Mahmoud; Saleem, Talha; Afzal, Saira; Alqaisi, Sura; Saand, Aisha R.; Najjar, Hanan Al.; Griffiths, Lori; Han, Xiaozhen; Wang, Xiaofeng; Perez-Protto, Silvia; Abella, Benjamin S.; et al.
Abstract : IMPORTANCE: In-hospital cardiac arrest survival among coronavirus disease 2019 patients has been reported to range from 0% to 12%. These numbers are significantly lower than reported prepandemic in-hospital cardiac arrest survival rates of approximately 20–25% in the United States for non–coronavirus disease 2019 patients. OBJECTIVE: To assess the incidence of in-hospital cardiac arrest survival of coronavirus disease 2019 patients. DESIGN: A retrospective cohort study of adult patients with coronavirus disease 2019 subsequently found to have in-hospital cardiac arrest and underwent cardiopulmonary resuscitation (cardiopulmonary resuscitation). SETTING: Multiple hospitals of the Cleveland Clinic Health System. PATIENTS: All adult patients (age ≥ 18 yr) admitted to Cleveland Clinic Health System with a diagnosis of coronavirus disease 2019 who experienced in-hospital cardiac arrest requiring cardiopulmonary resuscitation. MEASUREMENTS AND MAIN RESULTS: From March 01, 2020 to October 15, 2020, 3, 555 patients with coronavirus disease 2019 were hospitalized; 1, 372 were admitted to the ICU; 58 patients had in-hospital cardiac arrest. Median age of this cohort was 66.5 years (interquartile range, 55.0–76.0 yr). Patients were predominantly male (62.5%), White (53.4%), with a median body mass index of 29.7 (interquartile range, 25.8–34.6). Most in-hospital cardiac arrests were in critical care environments (ICU), 51 of 58 (87.9%); seven of 58 (12.1%) were on ward locations. Thirty-four of 58 patients (58.6%) were on mechanical ventilation prior to in-hospital cardiac arrest with a median duration of mechanical ventilation of 9 days (interquartile range, 2–18 d). Twenty-four of 58 patients (44%) were on vasopressors prior to arrest. Initial arrest rhythm was pulseless electrical activity at (63.8%), asystole (29.3%), and pulseless ventricular tachycardia/fibrillation (6.9%). Of the 58 patients, 35 (60.3%) attained return of spontaneous circulation, and 13 of 58 (22.4%) were discharged alive. CONCLUSIONS: We report a 22% survival to discharge after in-hospital cardiac arrest in coronavirus disease 2019 patients, a survival rate similar to before the coronavirus disease 2019 pandemic.